Excitatory Impact of Dental Occlusion on Dorsal Motor Nucleus of Vagus - Liu, Xin; Shi, Minghong; Ren, Haotian; Xie, Mianjiao; Zhang, Chunkui; Wang, Dongmei; Liu, Xiaodong; Li, Jinlian; Wang, Meiqing (Frontiers in Neural Circuits, 2021)
Neurons in the trigeminal mesencephalic nucleus (Vme) have axons that branch peripherally to innervate the orofacial region and project centrally to several motor nuclei in brainstem. The dorsal motor nucleus of vagus nerve (DMV) resides in the brainstem and takes a role in visceral motor function such as pancreatic exocrine secretion. The present study aimed to demonstrate the presence of a Vme-DMV circuit, activation of which would elicit a trigeminal neuroendocrine response. A masticatory dysfunctional animal model termed unilateral anterior crossbite (UAC) model created by disturbing the dental occlusion was used. Cholera toxin B subunit (CTb) was injected into the inferior alveolar nerve of rats to help identify the central axon terminals of Vme neurons around the choline acetyltransferase (ChAT) positive motor neurons in the DMV. The level of vesicular glutamate transporter 1 (VGLUT1) expressed in DMV, the level of acetylcholinesterase (AChE) expressed in pancreas, the level of glucagon and insulin expression in islets and serum, and the blood glucose level were detected and compared between UAC and the age matched sham-operation control mice. Data indicated that compared with the controls, there were more CTb/ VGLUT1 double labeled axon endings around the ChAT positive neurons in the DMV of UAC groups. Mice in UAC group expressed a higher VGLUT1 protein level in DMV, AChE protein level in pancreas, glucagon and insulin level in islet and serum, and higher postprandial blood glucose level, but lower fasting blood glucose level. All these were reversed at 15-weeks when UAC cessation was performed from 11-weeks (all, P < 0.05). Our findings demonstrated Vme-DMV circuit via which the aberrant occlusion elicited a trigeminal neuroendocrine response such as alteration in the postprandial blood glucose level. Dental occlusion is proposed as a potential therapeutic target for reversing the increased postprandial glucose level.